2015
DOI: 10.2217/mmt.15.26
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Complementary Role of Targeted Alpha Therapy in the Management of Metastatic Melanoma

Abstract: Standard treatments for metastatic melanoma have recently extended survival although many patients still succumb. Targeted alpha therapy (TAT) is a new therapeutic approach in which a cancer-targeting vector is labeled with an alpha-emitting radioisotope. Alpha-particles have the shortest range and highest energy transfer, and produce localized, high-density and lethal ionization damage to DNA. Thus, the targeted radiation can kill isolated cancer cells circulating in blood and lymphatic vessels, regress metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Ipilimumab (Yervoy®), pembrolizumab (Keytruda®) and nivolumab (Opdivo®) are worldwide-approved immune therapies for unresectable or metastatic melanoma [60]. Radiation therapies include Plaque brachytherapy, Stereotactic radiosurgery (SRS) with gamma knife and proton beam radiotherapy (PBT) [61]. For tumors where surgery is not a treatment of choice, intralesional TAT will be the best substitute and results in an increased survival rate.…”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Ipilimumab (Yervoy®), pembrolizumab (Keytruda®) and nivolumab (Opdivo®) are worldwide-approved immune therapies for unresectable or metastatic melanoma [60]. Radiation therapies include Plaque brachytherapy, Stereotactic radiosurgery (SRS) with gamma knife and proton beam radiotherapy (PBT) [61]. For tumors where surgery is not a treatment of choice, intralesional TAT will be the best substitute and results in an increased survival rate.…”
Section: Melanomamentioning
confidence: 99%
“…TAT therapy has been proven useful by disrupting tumor-feeding vasculature. Additionally, TAT with longer-lived radioisotopes (for example 225 Ac and 227 Th) will result in larger and homogenous radiation doses to tumors as compared to radioisotopes having short half-lives (for example 213 Bi with a half-life of 46 minutes) [61].…”
Section: Melanomamentioning
confidence: 99%
“…Endohedral metallofullerenes have been prepared for all of the lanthanides (except Pm) and a few of the actinides. , Further, fullerenes exhibit physical and chemical properties that make them well suited as nanocarriers of α-emitting actinides such as 225 Ac, a medically useful radionuclide. Extensive preclinical and clinical studies have shown the potential applications of α-particle-emitting radionuclides in a variety of cancer systems and targeted radiotherapy. In particular, the clinical trials for the treatment of acute myeloid leukemia, a therapy for recurrent glioblastoma, , and treatment of metastatic melanoma have all demonstrated the effectiveness of the α-emitter 225 Ac ( t 1/2 = 10 days) and its decay daughter, 213 Bi ( t 1/2 = 46 min), in killing cancer cells. The significant radiotoxicity associated with the actinides, particularly 225 Ac, emphasizes the need for special facilities for the safe handling of actinides.…”
Section: Introductionmentioning
confidence: 99%